The Relationship Between Emotion Regulation and Emotional Abuse in Dating College Students in Bandung: Hubungan Antara Regulasi Emosi dengan Emotional Abuse dalam Berpacaran pada Mahasiswi di Bandung - Rofifah, Aliza Athiya; Widyastuti, Widyastuti (Universitas Muhammadiyah Sidoarjo, 2022)
Emotional abuse is prone to occur in romantic relationships that have existed for more than 6 months. Unlike physical abuse, emotional abuse is carried out by women more than men. Emotional regulation is identified as one of the internal factors that can influence someone to do emotional abuse or not in a relationship. Therefore, this study aims to see the relationship between emotional regulation and emotional abuse in dating female students in Bandung using quantitative methods. The population selected in this study has certain criteria including female students aged 18-24 years, currently or have been in a relationship, and dating for a minimum of 6 months. The sample used is 213 samples. The measuring instrument for emotion regulation uses the DERS scale with a reliability of 0.910. While the emotional abuse measurement tool uses an emotional abuse scale with a reliability of 0.865. The sampling technique used purposive sampling. The results of hypothesis testing show (r = -.267**; p= 0.000) it can be concluded that the hypothesis is accepted so that there is a negative relationship between emotional regulation and emotional abuse so that the higher the emotional regulation, the lower the emotional abuse and vice versa. The contribution of emotion regulation to emotional abuse is 4.7%.